THE ROLE OF VARIOUS MODALITIES IN BREAST IMAGING - Prasad, Sachin N.; Houserkova, Dana (Biomedical papers, 2007)
Background: Breast cancer is the most common type of cancer in women worldwide. Mammography is considered the ``gold standard'' in the evaluation of the breast from an imaging perspective. Apart from mammography, ultrasound examination and magnetic resonance imaging are being offered as adjuncts to the preoperative workup. Recently, other new modalities like positron emission tomography, 99mTc-sestamibi scintimammography, and electrical impedance tomography (EIT) are also being offered. However, there is still controversy over the most appropriate use of these new modalities. Based on the literature, this review evaluates the role of various modalities used in the screening and diagnosis of breast cancer.Methods and Results: Based on relevant literatures this article gives an overview of the old and new modalities used in the field of breast imaging. A narrative literature review of all the relevant papers known to the authors was conducted. The search of literatures was done using pubmed and ovid search engines. Additional references were found through bibliography reviews of relevant articles. It was clear that though various new technics and methods have emerged, none have substituted mammography and it is still the only proven screening method for the breast as of date.Conclusion: From the literature it is clear that apropos modern radiology's impact on diagnosis, staging and patient follow-up, only one imaging technique has had a significant impact on screening asymptomatic individuals for cancer i.e.; low-dose mammography. Mammography is the only screening test proven in breast imaging. Positron emission tomography (PET) also plays an important role in staging breast cancer and monitoring treatment response. As imaging techniques improve, the role of imaging will continue to evolve with the goal remaining a decrease in breast cancer morbidity and mortality. Progress in the development and commercialisation of EIT breast imaging system will definitely help to promote other systems and applications based on the EIT and similar visualization methods. Breast ultrasound and breast magnetic resonance imaging (MRI) are frequently used adjuncts to mammography in today's clinical practice and these techniques enhance the radiologist's ability to detect cancer and assess disease extent, which is crucial in treatment planning and staging.
Keywords: Mammography/Ultrasonography/MRI/Breast screening/Breast mass/Breast imaging